2020
DOI: 10.1007/s15010-020-01521-5
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for screening, monitoring, prevention, and prophylaxis of infections in adult and pediatric patients receiving CAR T-cell therapy: a position paper

Abstract: Chimeric antigen receptor (CAR) T-cell therapy is one of the most promising emerging treatments for B-cell malignancies. Recently, two CAR T-cell products (axicabtagene ciloleucel and tisagenlecleucel) have been approved for patients with aggressive B-cell lymphoma and acute lymphoblastic leukemia; many other CART constructs are in research for both hematological and non-hematological diseases. Most of the patients receiving CART therapy will develop fever at some point after infusion, mainly due to cytokine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 95 publications
0
124
0
1
Order By: Relevance
“…Management of these adverse events was carried out according to the institutional guidelines in each center. Infectious complications were managed homogenously according to the Spanish consensus guidelines 16 …”
Section: Methodsmentioning
confidence: 99%
“…Management of these adverse events was carried out according to the institutional guidelines in each center. Infectious complications were managed homogenously according to the Spanish consensus guidelines 16 …”
Section: Methodsmentioning
confidence: 99%
“…Another guideline from the European Society for Blood and Marrow Transplantation recommends mold-active azole prophylaxis in patients with prior allogenic HCT, prior invasive aspergillosis, and those receiving corticosteroids [ 29 ]. Other groups have suggested that ≥4 prior anti-tumor treatment lines, CAR-T-cell dose of >2 × 10 7 /kg, prolonged neutropenia (≥3 weeks), and use of >1 dose of tocilizumab or the administration of other immunosuppressive agents (such as anakinra and siltuximab) for the management of CRS and ICANS should also warrant the use of mold-active antifungal prophylaxis [ 30 , 31 ].…”
Section: Anti-fungal Prophylaxis Following Car-t-cell Therapymentioning
confidence: 99%
“…It is standard practice to administer trimethoprim-sulfamethoxazole (or alternatives, such as dapsone, atovaquone, and monthly intravenous pentamidine) for 3–6 months after CAR-T-cell therapy to prevent PCP [ 6 , 30 , 31 ]. Given that many CAR-T-cell patients are expected to experience prolonged lymphopenia due to “on-target, off-tumor” effects of CAR-T-cells, these patients may be at risk for PCP beyond 6 months.…”
Section: Anti-fungal Prophylaxis Following Car-t-cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Strict recommendation for antifungal prophylaxis applies in limited cases (prior mold infection, ≥3 weeks of neutropenia before and after CAR T-cell therapy, dexamethasone use > 0.1 mg/Kg/day for at least a week) [ 175 , 176 ]. A recent position paper from Spain stated that PJP prophylaxis along with fluconazole should be standard for children under CAR T-cell therapy, while prophylaxis against filamentous fungi (posaconazole, nebulized liposomal amphotericin B or micafungin) should be added when two or more criteria are met: ≥four prior treatment lines, neutropenia prior to the infusion, CAR-T doses > 2 × 10 7 cells/Kg, previous IFD, tocilizumab and/or steroids use [ 177 ]. Tocilizumab use alone is a risk factor for IFDs and patients should be closely monitored [ 178 ].…”
Section: Chimeric Antigen Receptor (Car) T-cellsmentioning
confidence: 99%